Arginine off‐kilter: guanidinium is not as planar as restraints denote. Issue 12 (2nd December 2020) - Moriarty, Nigel W.; Liebschner, Dorothee; Tronrud, Dale E.; Adams, Paul D.
Abstract : The geometry of arginine shows more complexity than is accommodated by the standard restraints. Abstract : Crystallographic refinement of macromolecular structures relies on stereochemical restraints to mitigate the typically poor data‐to‐parameter ratio. For proteins, each amino acid has a unique set of geometry restraints which represent stereochemical information such as bond lengths, valence angles, torsion angles, dihedrals and planes. It has been shown that the geometry in refined structures can differ significantly from that present in libraries; for example, it was recently reported that the guanidinium moiety in arginine is not symmetric. In this work, the asymmetry of the N ϵ —C ζ —N η1 and N ϵ —C ζ —N η2 valence angles in the guanidinium moiety is confirmed. In addition, it was found that the C δ atom can deviate significantly (more than 20°) from the guanidinium plane. This requires the relaxation of the planar restraint for the C δ atom, as it otherwise causes the other atoms in the group to compensate by distorting the guanidinium core plane. A new set of restraints for the arginine side chain have therefore been formulated, and are available in the software package Phenix, that take into account the asymmetry of the group and the planar deviation of the C δ atom. This is an example of the need to regularly revisit the geometric restraint libraries used in macromolecular refinement so that they reflect the best knowledge of the structural chemistry of their components available at the time.